2022
DOI: 10.1111/bjh.18502
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of MYD88 and CXCR4 mutations assessed by droplet digital polymerase chain reaction in IgM monoclonal gammopathy of undetermined significance and smouldering Waldenström macroglobulinaemia

Abstract: Summary Waldenström macroglobulinaemia (WM) is characterized by recurrent somatic mutations in MYD88 and CXCR4 genes. However, limitations arise when analysing these mutations in IgM monoclonal gammopathy of undetermined significance (MGUS) or smouldering WM (SWM) given the lower tumour load. Here, we used droplet digital polymerase chain reaction (ddPCR) to analyse MYD88 L265P and CXCR4 S338* mutations (C1013G and C1013A) in unsorted bone marrow (BM) or cell‐free DNA (cfDNA) samples from 101 IgM MGUS and 69 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In a retrospective analysis of 54 patients from the FIL_BIOWM study they have demonstrated, for the rst time, that molecular remission is an independent predictor of PFS. Droplet digital polymerase chain reaction (ddPCR) assays for MYD88 have also been described 21,22 and may ultimately provide a reproducible platform for more widespread and routine use. They have been successfully used in a post-treatment pilot assessment, although no outcome data is yet available.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 54 patients from the FIL_BIOWM study they have demonstrated, for the rst time, that molecular remission is an independent predictor of PFS. Droplet digital polymerase chain reaction (ddPCR) assays for MYD88 have also been described 21,22 and may ultimately provide a reproducible platform for more widespread and routine use. They have been successfully used in a post-treatment pilot assessment, although no outcome data is yet available.…”
Section: Discussionmentioning
confidence: 99%